WOMEN SATISFACTION AND BEHAVIORAL INTENTION TOWARD HOSPITAL OBSTETRIC SERVICE - EKA WIDYA SHANTI (29009020) ; pembimbing : Dr. Ir. Mustika Sufiati Purwanegara, MSc., PUTU
This research was aimed to study which attributes/ elements would be the major considerations by women in selecting a hospital obstetric service and examine the relationship between women satisfaction and behavioral intention toward hospital obstetric service. Based on previous studies, the total quality service (TQS) was chosen as instrument for this research. By conducting exploratory factor analysis using promax rotation approach, the items were classified into two elements, structure and process. Then using structural equation modeling (SEM), the relationship between patient satisfaction and behavioral intention was analyzed. The result of the analysis showed that all the proposed hypotheses were accepted. Both structure and process elements had positive relationship with overall satisfaction. Overall satisfaction was also had positive impact to the behavioral intention, both intention to return or repurchase and intention to recommend. The limitation of the research is the present study tests the model using a single service industry, an exhaustive description of process quality could not be provided. This could be overcome in future studies by employing multiple service industries. This research provides a useful foundation whereby practitioners can appreciate the importance of process elements, in addition to structure elementsoll,k. In addition to clarify the attributes that are considered important by women inchoosing a hospital obstetric service, this research fulfils an identified information and resources need, and offers practical assistance to academics and practitioners in the field.